2017
DOI: 10.5194/tc-11-1987-2017
|View full text |Cite
|
Sign up to set email alerts
|

New methodology to estimate Arctic sea ice concentration from SMOS combining brightness temperature differences in a maximum-likelihood estimator

Abstract: Abstract. Monitoring sea ice concentration is required for operational and climate studies in the Arctic Sea. Technologies used so far for estimating sea ice concentration have some limitations, for instance the impact of the atmosphere, the physical temperature of ice, and the presence of snow and melting. In the last years, L-band radiometry has been successfully used to study some properties of sea ice, remarkably sea ice thickness. However, the potential of satellite Lband observations for obtaining sea ic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…6). The observational sea ice concentration product ASI (ARTIST Sea Ice algorithm) (Kaleschke et al, 2001;Spreen et al, 2008) shows a rapid freeze-up to 80 % sea ice coverage in just a few days. The brightness temperatures of SMOS measurements and the KA2010 and MA2013 models show high agreement with some exceptions on the first days of the freezing period, which starts around the 25 October.…”
Section: Radiative Transfer Model Sensitivity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…6). The observational sea ice concentration product ASI (ARTIST Sea Ice algorithm) (Kaleschke et al, 2001;Spreen et al, 2008) shows a rapid freeze-up to 80 % sea ice coverage in just a few days. The brightness temperatures of SMOS measurements and the KA2010 and MA2013 models show high agreement with some exceptions on the first days of the freezing period, which starts around the 25 October.…”
Section: Radiative Transfer Model Sensitivity Studymentioning
confidence: 99%
“…Consequently, sea ice thickness data sets using SMOS measurements have been produced operationally for the Arctic based on retrieval algorithm developed at the University of Hamburg (Kaleschke et al, 2012;Tian-Kunze et al, 2014). Other sea ice parameters estimated from L-band observations comprise sea ice concentration (Gabarro et al, 2017) and snow coverage on thick sea ice (Maaß et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The SIC has been retrieved with satellite microwave radiometer data since the 1970s, and the daily estimates of the global sea ice area and extent from these data are one of the longest continuous climate records (Stocker et al, ; Tonboe et al, ). Microwave frequency channels spanning from 1 to nearly 100 GHz are used for SIC retrieval (Gabarro et al, ; Ivanova et al, ). Recently, in an evaluation of over 20 different SIC algorithms (not including L band), it was found that the algorithm using 6.9‐GHz data had the lowest noise level of all the algorithms (Ivanova et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The L1B dataset contains the Fourier components of the Brightness Temperatures (TB) at the antenna reference frame. By applying an inverse Fourier transform, we obtain TB snapshots (i.e., an interferometric TB image) [25]. TBs are referenced using an Equal-Area Scalable Earth (EASE) Northern Hemisphere grid of 25 km resolution.…”
Section: Smos Datamentioning
confidence: 99%